Nancy Bookidis and Elizabeth G. Pemberton. The sanctuary of Demeter and Kore, the Greek lamps and offering trays - van der Enden, Mark (Journal of Greek Archaeology, 2016)
Nancy Bookidis and Elizabeth Pemberton’s the Greek Lamps and Offering Trays is a fine new addition to the Corinth series and another piece of the puzzle that is the sanctuary of Demeter and Kore. Following the six preceding volumes that detail the archaeology, inscriptions and topography of the site, the Greek Lamps and Offering Trays presents another detailed look at a particular aspect of material culture from the Demeter and Kore sanctuary. Focussed on Greek lamps and so-called offering trays this volume marvellously succeeds in furthering our understanding of the sanctuary and its associated material culture and is an excellent companion to the earlier volumes detailing the Greek and Roman pottery and terracottas recovered from the site. Corinth XVIII.7 is composed of five chapters and divided into two parts.